The prognostic value of skeletal muscle index on clinical and survival outcomes after cytoreduction and HIPEC for peritoneal metastases from colorectal cancer: A systematic review and meta-analysis. Issue 3 (March 2022) - Di Giorgio, Andrea; Rotolo, Stefano; Cintoni, Marco; Rinninella, Emanuele; Pulcini, Gabriele; Schena, Carlo Alberto; Ferracci, Federica; Grassi, Futura; Raoul, Pauline; Moroni, Rossana; Pacelli, Fabio; Gasbarrini, Antonio; et al.
Abstract: Background: Cytoreductive surgery (CRS) and hypertermic intraperitoneal chemotherapy (HIPEC) represent the most effective strategy to manage peritoneal metastases (PM). This systematic review and meta-analysis aimed to assess the impact of body composition on clinical outcomes in patients with PM. Methods: A systematic literature search was performed using Medline, Web of Science and EMBASE databases from inception to the 20 st August 2020. Data were independently extracted by 3 authors. Newcastle-Ottawa Scale was used to assess quality and risk of bias of studies. Pooled analyses were performed using Mantel-Haenszel method to estimate overall effect size with mean differences or odd ratios (ORs) and 95% confidence interval (CI). The primary outcome was postoperative complication (POC) rate, while secondary outcomes were severe POC and postoperative mortality. Results: A total of 4 studies were included in the systematic review and meta-analysis, including 582 patients. A significant association between low skeletal muscle mass and POC was found (OR 1.45, 95% CI 1.04 to 2.03; p = 0.03), while no differences were found in terms operative time, estimated blood loss, length of hospital stay, and postoperative mortality (p > 0.05). Conclusions: Low skeletal muscle mass at diagnosis is a valid prognostic factor for POC development in colorectal and PM patients undergoing CRS. Prospective and larger studies are needed to better investigate the role of CT scan derived body composition and to understand how to implement this tool in clinical practice.